Composition-segmented BiSbTe thermoelectric generator fabricated by multimaterial 3D printing. (March 2021) - Yang, Seong Eun; Kim, Fredrick; Ejaz, Faizan; Lee, Gi Seung; Ju, Hyejin; Choo, Seungjun; Lee, Jungsoo; Kim, Gyeonghun; Jung, Soo-ho; Ahn, Sangjoon; Chae, Han Gi; Kim, Kyung Tae; et al.
Abstract: Segmented thermoelectric generators (TEGs) comprising multiple TE elements can operate over a large thermal gradient without inherent conversion efficiency ( ZT ) losses of materials. However, despite excellent theoretical efficiencies, the performance of actual segmented TEGs are critically affected by several challenges related to material incompatibility and limited design flexibility in conventional fabrication processes. Herein, we report the multi-material 3D printing of composition-segmented BiSbTe materials by the sequential deposition of all-inorganic viscoelastic TE inks containing Bi x Sb2 - x Te3 particles, tailored with Sb2 Te4 2− chalcogenidometallate binders. The peak ZT s of the 3D-printed materials controllably shifted from room temperature to 250 °C by composition engineering of Bi x Sb2 - x Te3 particles. We fabricated the optimally designed TEG comprising the 3D-printed, composition-segmented tri-block Bi0.55 Sb1.45 Te3 /Bi0.5 Sb1.5 Te3 /Bi0.35 Sb1.65 Te3 TE leg, which extends the peak ZT s and satisfies full compatibility across the entire temperature range, realizing a record-high efficiency of 8.7% under the temperature difference of 236 °C. Our approach offers a promising strategy to optimize segmented TEGs. Graphical Abstract: ga1 Highlights: We developed a multi-material 3D printing process of composition-engineered BiSbTe materials by the sequential deposition. Organics-free viscoelastic colloid inks containing Bi x Sb2- x Te3 TE particles with controlled compositions. The maximum power density of the segmented TEG was 259.3 mW/cm 2 (Δ T  = 236 °C) and the conversion efficiency reached 8.7%. This approach will pave a new way for designing high-performance TEGs in a cost-effective manner.